SOME MORPHOMETRIC OBSERVATIONS OF COCCINELLID PROPYLES DISSECTA (MULSANT) COLLECTED FROM NAVSARI, SOUTH GUJARAT - JADHAV, DARSHANA S.; SHUKLA, ABHISHEK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
An investigation was carried out during 2011-13 on the morphometrics of ladybird beetle, Propyles dissecta (Mulsant). The findings indicated that the average body length of P. dissecta was 3.81 mm and width was 2.86 mm, the head length was 0.98 mm and width was 1.07 mm. antennal length was 1.30 mm, thorax length was 1.87 mm and width was 2.72 mm, fore leg length was 4.30 mm, middle leg was 3.05 mm, hind leg length was 4.20 mm, elytra length was 3.49 mm and width was 2.01 mm, hind wing length was 5.44 mm and width was 2.00 mm and abdomen length was 2.24 mm and width was 2.87 mm.